BIMBINGAN KELOMPOK BERBASIS TATA NILAI BUDAYA LAMPUNG UNTUK MENINGKATKAN TINGKAH LAKU PROSOSIAL SISWA - Fitria, Nita (JURNAL FOKUS KONSELING, 2015)
AbstractProsocial behavior is a concern which is described by the willingness to help others, empathy and generosity. To develop this attitude, it needsguidance and counseling service with a strong social values and culture. This study aims to know the effectiveness of group guidance based on Lampung cultural values to increase the prosocial behavior. These samples included 15 that randomized from 76 students. The research method that writer used is the pre-experimental designs. Based on the data analysis of prosocial behavior scores before of the students following group guidance based on Lampung value cultural services in 1929, then after following the service the scores increased to 2631. So this means that Null Hypothesis (Ho) is rejected and Alternative Hypothesis (Ha) is accepted. It can be included that the group guidance model based on Lampung cultural values is effective to improve the student prosocial behavior.Â Â Keyword : group guidance, prosocial behavior, cultural valuesÂ